Saving taxes through foreign plant ownership - Peter Egger; Wolfgang Eggert; Hannes Winner (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper analyzes to which extent foreign plant ownership involves lower tax payments than domestic plant ownership. We employ a model of endogenous foreign subsidiary ownership to derive a set of empirically testable hypotheses about the differential taxation of foreign- and domestically-owned subsidiaries. We assess these hypotheses in a data- set of 33,577 European foreign- and domestically-owned manufacturing plants. We identify a significant tax-saving of endogenous foreign owner- ship. On average, foreign owners pay 594 Euros per employee or about 56 percent less than domestic owners of similar subsidiaries. This effect is larger in thinner markets with fewer plants, in markets with a greater relative presence of foreign owners, and for foreign owners of larger plants.
Keywords: H25; H73; F23; C21; 330; Unternehmensbesteuerung; Multinationales Unternehmen; Auslandsniederlassung; Steuerbelastung; EU-Staaten